Wearing the Niqab: Muslim Women in the UK and the US - Nurhayati, Elis (Muslim Politics Review, 2023)
Wearing the Niqab: Muslim Women in the UK and the US, Anna Piela (New York: Bloomsbury Publishing, 2021) This book is about narratives on various topics voiced out by niqab wearers in the private and public spheres, including in the mainstream media, in the United Kingdom (UK) and United States (US). Featured narratives include ones on religious agency, identity, social interaction, community, and urban spaces. The author, Anna Piela, situates the narratives in the social and political context in the two countries.